2023
DOI: 10.2147/jir.s398291
|View full text |Cite
|
Sign up to set email alerts
|

The Involvement of Glucose and Lipid Metabolism Alteration in Rheumatoid Arthritis and Its Clinical Implication

Abstract: Obviously, immune cells like T cells and macrophages play a major role in rheumatoid arthritis (RA). On one hand, the breakdown of immune homeostasis directly induces systemic inflammation; on the other hand, these cells initiate and perpetuate synovitis and tissue damages through the interaction with fibroblast-like synoviocytes (FLS). In recent years, the pathological link between metabolic disorders and immune imbalance has received increasing attention. High energy demand of immune cells leads to the accum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 181 publications
0
2
0
Order By: Relevance
“…More and more studies are now showing that disturbed glucose metabolism promotes the development of RA. 10,11 Also with the improvement of people's living standards, the burden of metabolic diseases has increased most. 12 By observing the liver RNA-seq results, it was also found that AA rats had disturbed hepatic metabolism, although without hyperglycemia in the Model group.…”
Section: Discussionmentioning
confidence: 99%
“…More and more studies are now showing that disturbed glucose metabolism promotes the development of RA. 10,11 Also with the improvement of people's living standards, the burden of metabolic diseases has increased most. 12 By observing the liver RNA-seq results, it was also found that AA rats had disturbed hepatic metabolism, although without hyperglycemia in the Model group.…”
Section: Discussionmentioning
confidence: 99%
“…However, biologic agents are expensive, and approximately 30–40% of patients do not respond well, accompanied with increased risk of infections. 4 , 5 Thus, novel therapeutic strategies for RA are urgently needed.…”
Section: Introductionmentioning
confidence: 99%
“…During FLS activation, metabolic changes are considered a key factor in their functional alteration ( 9 ). Multiple lines of evidence indicate that RA FLS cells exhibit considerable differences in protein, glucose, and lipid metabolism than normal synovial FLS cells ( 6 , 10 12 ). This abnormal metabolism is involved in RA pathogenesis, reflecting FLS adaptation to inflammatory and hypoxic conditions during excessive proliferation and phenotypic abnormalities.…”
Section: Introductionmentioning
confidence: 99%